Beyond Kulturkritik: Along the Supply Chain of Contemporary Capitalism - Brett Neilson (Culture Unbound: Journal of Current Cultural Research, 2014)
Notions of Kulturkritik stemming from twentieth century accounts of mass con-sumption present culture as an effect of the mode or relations of production. Culture becomes the means by which capitalism imposes itself as an ideological system. This paper asks how Kulturkritik might be revived or revisited in the current moment of capitalist globalisation. Focusing on changes to production systems introduced by the growth of logistics and supply chain management, it argues that cultural processes of translation, signification, communication and argument have become deeply and materially embedded in the development of capitalism. Particular attention is paid to how infrastructure and technology shape relations of capital and labour. The paper asks how the subjective force of labour can exploit the vulnerabilities inherent in supply chains and confront the networked forms of organisation that enable contemporary capitalism. Overall the aim is to establish a role for culture in struggles against capitalism and to rethink the place of critique and ideology in the wake of such an approach.